Impact of heat recovery and thermal load control on combined heat and power (CHP) performance - Maghami M.R.; Mutambara A.G.O.; Gomes C.; Pasupuleti J. (Elsevier Ltd, 2025)
This research assesses the energy efficiency and techno-economic viability of a Combined Heat and Power (CHP) system designed for a typical building that meets both its electrical (97 kWh/d) and thermal (92 kWh/d) loads. The CHP system comprises wind turbines (WT), photovoltaic panels (PV), batteries, micro gas turbines (MGT), and boilers, which are evaluated for their techno-economic performance. To enhance the system's efficiency and minimize energy wastage in CHP, two strategies, namely heat recovery (HR) from MGT and Thermal Load Control (TLC) for converting surplus renewable power generation into thermal energy, are implemented. Four case studies are conducted to analyze the impact of each strategy on the CHP system's performance. The optimization of hybrid renewable energy systems, considering the overall system's economic performance, is achieved through the integration of MATLAB and HOMER PRO. The study reveals that the incorporation of TLC and HR results in significant reductions in the Cost of Energy (COE), Net Present Cost (NPC), CO2 emissions, loss of Power Supply (LPS), and energy sizing while increasing the renewable fraction in the CHP system. Sensitivity analysis is performed on the capital cost of components, TLC, and HR variations, demonstrating their substantial influence on the economic performance of CHP. The cash flow results show that the integration of these two components reduces the system cost by 25 %. It is also shown that almost 70 % of the CC of the system is related to PV and batteries. The proposed strategies and findings provide valuable insights for enhancing the reliability and techno-economic evaluations of hybrid renewable. ? 2024 The Authors